A low shrinkage wrinkle-resistant nylon fabric and its preparation method and application in zippers
By combining functionalized graphene and organic antistatic agents on nylon fabrics, combined with the finishing and dyeing process of composite finishing liquid, a low-shrinkage-resistant nylon cloth is prepared, which solves the problem of easy storage of nylon fabrics after storage. The problem of deformation in wrinkles and acidic environments achieves efficient anti-static, wrinkle and low shrinkage effects.
Patent Information
- Application Number
- CN202411479239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Nylon fabrics are prone to wrinkles after being stored and folded, and are deformed and rolled due to shrinkage and deformation during dyeing and finishing in an acidic environment, which causes the clothing to deform, affecting the use of zippers.
The preparation method of low-shrinkage anti-wrinkle nylon cloth is adopted, including functionalizing graphene and combining with organic antistatic agents, grafting on nylon 6 fibers, and improving the resistance of nylon cloth through composite finishing liquid. Electrostatic and wrinkle resistance, reducing shrinkage rate.
The long-term anti-static effect of nylon cloth is achieved, the mechanical properties and dimensional stability are improved, the shrinkage rate is reduced, and the deformation problem of clothing during use is reduced.
Smart Images

Figure CN118996852B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of garment accessories processing, in particular to a low-shrinkage wrinkle-resistant nylon fabric and a preparation method thereof and application in a zipper. Background Art
[0002] Zippers are one of the common components of clothing accessories. The tape in the zipper is a flexible tape woven from yarns through a series of processes such as threading and warping according to patterns. It is used to carry components such as chain teeth. At present, nylon is one of the main raw materials for zipper tapes. However, nylon fabrics are very easy to wrinkle after being stored and folded, and when nylon fabrics are dyed and finished in an acidic environment, they will deform and curl due to strong shrinkage, which will cause the clothing to bulge and deform, affecting the use of zippers. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for preparing a low shrinkage and wrinkle-resistant nylon fabric, comprising the following steps:
[0004] Step (1), modifying graphene with L-cysteine to obtain functionalized graphene;
[0005] Step (2), lactobionic acid reacts with N,N-dimethyldipropylenetriamine to obtain an intermediate; the intermediate reacts with chloropropane to obtain an organic antistatic agent; functionalized graphene is combined with the organic antistatic agent to obtain a composite antistatic agent;
[0006] Step (3), first modifying nylon 6 to prepare modified nylon 6, and then treating the modified nylon 6 with a composite antistatic agent to obtain composite modified nylon 6;
[0007] Step (4), the composite modified nylon 6 is melt-spun to obtain composite modified nylon 6 fibers, the composite modified nylon 6 fibers are spun into yarns, the yarns are heat-set and then dehydrated, and then woven into grey fabrics;
[0008] Step (5), after the grey cloth is treated with a composite finishing liquid and dyed, it is then subjected to product finalization and pre-shrinkage finishing to obtain a low shrinkage and wrinkle-resistant nylon cloth; wherein the method for preparing the composite finishing liquid comprises the following steps: step S1, modifying sericin with acryloyl chloride to obtain modified sericin; step S2, modifying nanosilver with a silane coupling agent KH-550 to obtain modified nanosilver; the modified sericin reacts with the modified nanosilver to obtain a hybrid modified sericin; step S3, using 1,3,5-triacryloylhexahydro-1,3,5-triazine and hybrid modified sericin as raw materials to prepare a composite finishing liquid.
[0009] Preferably, in step (1), the functionalized graphene preparation method comprises dispersing graphene powder in an ethanol aqueous solution with a volume fraction of 70%, purging with nitrogen and ultrasonically treating for 20-40 minutes, adding L-cysteine and azobisisobutyronitrile, purging with nitrogen and ultrasonically treating for 20-40 minutes respectively, heating to 60-70°C for reflux reaction for 8-12 hours, and after the reaction is completed, centrifuging, washing, and drying; wherein the mass ratio of graphene powder, ethanol aqueous solution, L-cysteine, and azobisisobutyronitrile is (5-10): (500-800): (2-5): (0.4-0.6); in the above process, the graphene is functionalized by the thiol-ene click reaction between L-cysteine and graphene, and carboxyl groups and amino groups are introduced on the graphene surface.
[0010] Preferably, in step (2), the preparation method of the organic antistatic agent is as follows: lactobionic acid and N,N-dimethyldipropylenetriamine are added to ethanol, heated to 150-170°C in a nitrogen atmosphere for reflux reaction for 10-15h, rotary evaporation, washing, and drying to obtain an intermediate; wherein the mass ratio of lactobionic acid, N,N-dimethyldipropylenetriamine, and ethanol is (11.6-17.4): (19.1-34.4): (300-500); the intermediate, propylene glycol, and methanol are mixed, The reaction is carried out at 35-42°C for 20-30 hours, followed by rotary evaporation, washing and drying to obtain an organic antistatic agent; wherein the mass ratio of the intermediate, propylene chloride and methanol is (27.5-33): (20-30): (300-500); in the above process, the carboxyl group of lactobionic acid reacts with the amino group of N,N-dimethyldipropylenetriamine to form an intermediate, and the intermediate is quaternized with propylene chloride to synthesize an organic antistatic agent containing a diquaternary ammonium salt structure, and the organic antistatic agent also contains a polyhydroxy structure introduced by lactobionic acid.
[0011] Preferably, in step (2), the preparation method of the composite antistatic agent is as follows: functionalized graphene, an organic antistatic agent, p-toluenesulfonamide and N,N-dimethylformamide are mixed, heated to 120-140°C in a nitrogen atmosphere, stirred for reaction for 3-5 hours, and after the reaction is completed, centrifuged. The obtained precipitate is washed with saturated sodium bicarbonate and deionized water, and dried to obtain a composite antistatic agent; wherein the mass ratio of the functionalized graphene, the organic antistatic agent, p-toluenesulfonamide and N,N-dimethylformamide is (5-8): (2.1-4.2): (0.05-0.1): (150-250); in the above process, the carboxyl group on the surface of the functionalized graphene undergoes an esterification reaction with the hydroxyl group in the organic antistatic agent, so that the organic antistatic agent is combined with the inorganic graphene to form a composite antistatic agent.
[0012] Preferably, in step (3), the preparation method of the composite modified nylon 6 comprises: crushing nylon 6 slices into nylon 6 powder with a particle size of 30-80 μm, mixing the nylon 6 powder with 3-(4-glycidylbutoxy)-1,2-propylene glycol at a mass ratio of 1:(0.06-0.1), and mixing at 230-240° C. and a rotation speed of 30-50 rpm for 10-20 min to obtain modified nylon 6; mixing modified nylon 6, dibutyltin dilaurate, a composite antistatic agent, and N,N-dimethylformamide, stirring for 30-60 min, adding dicyclohexylmethane diisocyanate at a speed of 0.3-0.6 mL / min, reacting at 55-65° C. for 2-4 h, filtering after the reaction is completed, washing the filter residue with acetone, and drying to obtain the composite modified nylon 6. Nylon 6, wherein the mass ratio of modified nylon 6, dibutyltin dilaurate, composite antistatic agent, N,N-dimethylformamide and dicyclohexylmethane diisocyanate is 1: (0.002-0.005): (0.05-0.15): (20-50): (0.02-0.03); in the above process, 3-(4-glycidylbutoxy)-1,2-propanediol and nylon 6 are combined through the chemical bond formed between the amide group and the epoxy group and the hydrogen bond formed between the amide group and the hydroxyl group to achieve the modification of nylon 6, and hydroxyl groups are introduced on the surface of nylon 6 to obtain modified nylon 6; the hydroxyl groups in the modified nylon 6 react with the hydroxyl groups in the composite antistatic agent under the cross-linking action of dicyclohexylmethane diisocyanate, and the composite antistatic agent is grafted on nylon 6 in the form of chemical bonds.
[0013] Preferably, in step (4), the melt spinning process conditions are: a spinneret with a micropore diameter of 0.18-0.22 mm and an aspect ratio of 3:1 is selected, the spinning temperature is 260-270°C, and the spinning traction speed is 3000-4000 m / min.
[0014] Preferably, in step (4), in the grey cloth: the yarn count of the warp yarn is 22-28 dTex, the warp density is 205-231 yarns / inch, and the yarn count of the weft yarn is 81-87 dTex, and the weft density is 42-48 yarns / inch.
[0015] Preferably, in step (4), the heat setting treatment process conditions are: heating to 80-140°C at a rate of 2.5-4°C / min, then heating to 120-180°C at a rate of 1°C / min, and keeping warm for 30-60 min.
[0016] Preferably, in step (5), the product shaping is performed using the same process as the heat setting treatment in step (4).
[0017] Preferably, in step (5), the dyeing and finishing method is: dyeing with acid dye at 80-90°C and standing for 2-3 hours; the amount of acid dye used is: 7-13g of dye material per 1kg of grey cloth.
[0018] Preferably, in the step (5), the pre-shrinkage finishing is carried out under the conditions of a pressure of 4-5 MPa, a temperature of 140-150° C., and a vehicle speed of 40-60 m / min.
[0019] Preferably, in step (5), the composite finishing liquid finishing method is as follows: immersing the dyed grey cloth in the finishing liquid, the bath ratio is 1:(15-20), the finishing temperature is 50-60°C, the finishing time is 20-40min, and after finishing, drying at 60-70°C for 1-3min, and then curing at 130-140°C for 2-5min.
[0020] Furthermore, in step (5), the method for preparing the composite finishing liquid comprises the following steps:
[0021] Step S1, adding sericin powder to a 0.13wt% sodium chloride aqueous solution, stirring until all solids are dissolved, adding acryloyl chloride at 0-5°C, stirring for reaction for 50-80min, stirring for reaction at room temperature for 100-150min, dialyzing, and freeze-drying to obtain modified sericin; wherein the mass ratio of sericin powder, sodium chloride aqueous solution, and acryloyl chloride is (1.8-3.6): (100-150): (0.07-0.14); in the above process, sericin contains abundant hydroxyl groups, carboxyl groups, and amino groups, and the amino groups in the sericin react with acryloyl chloride to introduce carbon-carbon double bonds into the sericin;
[0022] Step S2, adding a silane coupling agent KH-550 solution to a 2.5-10wt% nano-silver ethanol dispersion, stirring for 20-40 minutes, stirring and reacting at 60-80°C for 4-6 hours, centrifuging after the reaction, washing, and drying to obtain modified nano-silver; wherein the silane coupling agent KH-550 solution is obtained by mixing silane coupling agent KH-550, deionized water, and ethanol in a mass ratio of 2.5:1:9, and then adjusting the pH to 4 with acetic acid; the mass ratio of silane coupling agent KH-550 to nano-silver is (0.01-0.02):1; in the above process, the silanol after hydrolysis of the silane coupling agent KH-550 combines with the nano-silver, and an amino group is introduced on the nano-silver; the modified sericin and the modified nano-silver are added to the water and stirred for 20-40 minutes , at room temperature, a 0.2 g / mL 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution is added dropwise at a rate of 1.5-2.5 mL / min, and the mixture is stirred for reaction for 20-25 h. After the reaction is completed, the upper layer of liquid is removed by centrifugation, and the mixture is washed and dried to obtain a hybrid modified sericin; wherein the amount ratio of modified sericin, modified nanosilver, water, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution is (2-3) g: (0.8-1.2) g: (100-200) g: (3-4.5) mL; in the above process, the carboxyl group in the modified sericin reacts with the amino group on the modified nanosilver, and the nanosilver is connected to the modified sericin by forming a covalent bond, thereby improving the compatibility of the nanosilver and sericin;
[0023] Step S3, adding 1,3,5-triacryloylhexahydro-1,3,5-triazine to a sodium bicarbonate aqueous solution with a concentration of 20 g / L, heating to 50-60° C., stirring for 20-40 min, and then adding hybrid modified sericin to obtain a composite finishing solution, wherein the concentration of 1,3,5-triacryloylhexahydro-1,3,5-triazine in the composite finishing solution is 80-120 g / L, and the concentration of the hybrid modified sericin is 5-15 g / L; in the above process, 1,3,5-triacryloylhexahydro-1,3,5-triazine in the composite finishing solution has three identical active carbon-carbon double bonds that can cross-link with the hydroxyl groups in the composite modified nylon 6 fiber and the hybrid modified sericin, and the amino group, carboxyl group, hydroxyl group and carbon-carbon double bond in the hybrid modified sericin can form strong cross-links with the amino group and hydroxyl group of the composite modified nylon 6 fiber through chemical bonds or hydrogen bonds.
[0024] The low-shrinkage anti-wrinkle nylon cloth is prepared by the method for preparing the low-shrinkage anti-wrinkle nylon cloth.
[0025] Application of the low shrinkage and wrinkle-resistant nylon fabric in zippers.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention uses the carboxyl group of lactobionic acid and N,N-dimethyldipropylenetriamine as raw materials to prepare an intermediate, and the intermediate is quaternized with chloropropane to synthesize an organic antistatic agent rich in hydroxyl and diquaternary ammonium salt structure. The hydrophilic hydroxyl group can absorb moisture in the air to form a conductive water layer, and the stable ammonium cation in the quaternary ammonium salt structure increases the charge density of the polymer, and increases the polarity of the organic antistatic agent, thereby improving the antistatic performance; the graphite phase is functionalized to introduce hydrophilic carboxyl groups and amino groups, and a reactive group (carboxyl group) is provided for its combination with the organic antistatic agent, so that the covalent combination of the organic antistatic agent and the inorganic antistatic agent is achieved, so that the composite antistatic agent has a more excellent antistatic effect, and then the composite antistatic agent is grafted on nylon 6 in the form of a chemical bond, so that the final nylon cloth has a long-lasting antistatic effect, and solves the interface compatibility problem between inorganic graphene and nylon 6; further, the addition of graphene can also improve the mechanical properties and dimensional stability of nylon 6, thereby improving the mechanical properties and wrinkle resistance of the nylon cloth and reducing the shrinkage rate;
[0028] 2. The present invention prepares a composite finishing liquid by mixing hybrid modified sericin with 1,3,5-triacryloylhexahydro-1,3,5-triazine. In the process of finishing nylon grey cloth, the active carbon-carbon double bonds of 1,3,5-triacryloylhexahydro-1,3,5-triazine can cross-link with the composite modified nylon 6 fiber and the hydroxyl groups in the hybrid modified sericin, and the amino group, carboxyl group, hydroxyl group and carbon-carbon double bonds in the hybrid modified sericin can cross-link with the amino group and hydroxyl group of the composite modified nylon 6 fiber through chemical bonds or hydrogen bonds, and strengthen the cross-linking between nylon fibers, prevent mutual movement between fibers, improve the wrinkle resistance of nylon cloth, and reduce shrinkage rate; further, the introduction of hydrophilic groups (amino group, carboxyl group, hydroxyl group) in the hybrid modified sericin and the addition of conductive nanosilver can cooperate with the composite antistatic agent to further improve the antistatic performance of nylon cloth. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a process flow chart of a method for preparing a low shrinkage and wrinkle-resistant nylon fabric of the present invention;
[0030] Figure 2 It is a comparison chart of shrinkage test of low shrinkage and wrinkle-resistant nylon fabrics of Examples 2-4 of the present invention and Comparative Examples 4-10;
[0031] Figure 3 It is a comparison chart of wrinkle recovery angle test of low shrinkage and wrinkle-resistant nylon fabrics of Examples 2-4 of the present invention and Comparative Examples 4-10;
[0032] Figure 4 It is a comparison chart of the surface resistivity test of the low shrinkage and wrinkle-resistant nylon fabrics of Examples 2-4 of the present invention and Comparative Examples 4-10. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment discloses a method for preparing a composite finishing liquid, comprising the following steps:
[0036] Step S1, adding 2.7 g of sericin powder to 120 g of 0.13 wt % sodium chloride aqueous solution, stirring until the solid is completely dissolved, adding 0.11 g of acryloyl chloride at a temperature of 3° C., maintaining the temperature at 3° C. and stirring for reaction for 70 min, stirring for reaction at room temperature for 120 min, dialyzing the reaction mixture in a dialysis bag with a molecular weight cutoff of 3500 for 3 days, and finally freeze-drying the obtained product to obtain modified sericin;
[0037] Step S2, adding a silane coupling agent KH-550 solution to a 6.2wt% nano-silver ethanol dispersion, stirring for 30 minutes, stirring and reacting at 70°C for 5 hours, centrifuging after the reaction, washing, and drying to obtain modified nano-silver; wherein the silane coupling agent KH-550 solution is obtained by mixing silane coupling agent KH-550, deionized water, and ethanol in a mass ratio of 2.5:1:9, and then adjusting the pH to 4 with acetic acid; the mass ratio of silane coupling agent KH-550 to nano-silver is 0.015:1; adding 2.5g of modified sericin and 1g of modified nano-silver to 150g of water, stirring for 30 minutes, and at room temperature, dropping 3.8mL of a 0.2g / mL 1-ethyl-(3-dimethylaminopropyl) carbodiimide aqueous solution at a speed of 2mL / min, stirring and reacting for 22h, and after the reaction is completed, centrifuging to remove the upper liquid, washing, and drying to obtain hybrid modified sericin;
[0038] Step S3, adding 1,3,5-triacryloylhexahydro-1,3,5-triazine to a sodium bicarbonate aqueous solution with a concentration of 20 g / L, heating to 55° C., stirring for 30 minutes, and then adding hybrid modified sericin to obtain a composite finishing solution, wherein the concentration of 1,3,5-triacryloylhexahydro-1,3,5-triazine in the composite finishing solution is 100 g / L, and the concentration of the hybrid modified sericin is 10 g / L.
[0039] Example 2
[0040] This embodiment discloses a method for preparing a low shrinkage and wrinkle-resistant nylon fabric, comprising the following steps:
[0041] Step (1), dispersing 5 g of graphene powder in 500 g of 70% ethanol aqueous solution, purging with nitrogen and ultrasonically treating for 20 min, adding 2 g of L-cysteine and 0.4 g of azobisisobutyronitrile, purging with nitrogen and ultrasonically treating for 20 min each, heating to 60° C. and reflux reaction for 8 h, after the reaction is completed, centrifuging, washing, and drying to obtain functionalized graphene;
[0042] Step (2), adding 11.6g lactobionic acid and 19.1g N,N-dimethyldipropylenetriamine to 300g ethanol, heating to 150°C for reflux reaction for 10h in a nitrogen atmosphere, removing the solvent by rotary evaporation, washing the obtained product with ether three times, and drying to obtain an intermediate; mixing 27.5g of the intermediate, 20g of chloropropane, and 300g of methanol, reacting at 35°C for 20h, rotary evaporation to remove the solvent, washing the obtained product with ether three times, and drying to obtain an organic antistatic agent; mixing 5g of functionalized graphene, 2.1g of organic antistatic agent, 0.05g of p-toluenesulfonamide, and 150g of N,N-dimethylformamide, heating to 120°C for stirring reaction for 3h in a nitrogen atmosphere, centrifuging after the reaction, washing the obtained precipitate with saturated sodium bicarbonate and deionized water, and drying to obtain a composite antistatic agent;
[0043] Step (3), crushing nylon 6 slices into nylon 6 powder with a particle size of 30 μm, mixing the nylon 6 powder with 3-(4-glycidylbutoxy)-1,2-propylene glycol at a mass ratio of 1:0.06, and mixing at 230° C. and a rotation speed of 30 rpm for 10 min to obtain modified nylon 6; mixing modified nylon 6, dibutyltin dilaurate, a composite antistatic agent, and N,N-dimethylformamide, stirring for 30 min, adding dicyclohexylmethane diisocyanate dropwise at a rate of 0.3 mL / min, reacting at 55° C. for 2 h, filtering after the reaction is completed, washing the filter residue with acetone, and drying to obtain composite modified nylon 6, wherein the mass ratio of modified nylon 6, dibutyltin dilaurate, composite antistatic agent, N,N-dimethylformamide, and dicyclohexylmethane diisocyanate is 1:0.002:0.05:20:0.02;
[0044] Step (4), melt spinning the composite modified nylon 6 to obtain composite modified nylon 6 fiber, spinning the composite modified nylon 6 fiber into yarns of different finenesses, dehydrating the yarns after heat setting treatment, and then weaving them into grey cloth; wherein, the melt spinning process conditions are: a spinneret with a micropore diameter of 0.18 mm and an aspect ratio of 3:1 is selected, the spinning temperature is 260°C, and the spinning traction speed is 3000m / min; the heat setting process conditions are: heating to 80°C at a rate of 2.5°C / min, then heating to 120°C at a rate of 1°C / min, and keeping warm for 30min; in the grey cloth: the yarn count of the warp yarn is 22dTex, the warp density is 231 yarns / inch, and the yarn count of the weft yarn is 81dTex, and the weft density is 48 yarns / inch;
[0045] Step (5), after the grey cloth is treated with a composite finishing liquid and dyed, it is then subjected to product shaping and pre-shrinking finishing to obtain a low shrinkage and wrinkle-resistant nylon cloth; wherein the product shaping adopts the same process method as the heat setting treatment in step (4); the pre-shrinking finishing is carried out using a rubber blanket pre-shrinking machine under the conditions of a pressure of 4 MPa and a temperature of 140° C., and a speed of 40 m / min; the dyeing and finishing method is: dyeing with an acid dye at 80° C. and standing for 2 hours; the amount of acid dye used is: 7 g of dye material per 1 kg of grey cloth; the composite finishing liquid finishing method is: immersing the dyed grey cloth in the finishing liquid, the bath ratio is 1:15, the finishing temperature is 50° C., the finishing time is 20 min, and after the finishing is completed, it is first dried at 60° C. for 1 min, and then cured at 130° C. for 2 min.
[0046] Example 3
[0047] This embodiment discloses a method for preparing a low shrinkage and wrinkle-resistant nylon fabric, comprising the following steps:
[0048] Step (1), dispersing 10 g of graphene powder in 800 g of 70% ethanol aqueous solution, purging with nitrogen and ultrasonically treating for 40 min, adding 5 g of L-cysteine and 0.6 g of azobisisobutyronitrile, purging with nitrogen and ultrasonically treating for 40 min each, heating to 70° C. and reflux reaction for 12 h, after the reaction is completed, centrifuging, washing, and drying to obtain functionalized graphene;
[0049] Step (2), adding 17.4g lactobionic acid and 34.4g N,N-dimethyldipropylenetriamine to 500g ethanol, heating to 170°C in a nitrogen atmosphere, reflux reaction for 15h, rotary evaporation to remove the solvent, washing the obtained product with ether 5 times, and drying to obtain an intermediate; mixing 33g of the intermediate, 30g of chloropropane, and 500g of methanol, reacting at 42°C for 30h, rotary evaporation to remove the solvent, washing the obtained product with ether 5 times, and drying to obtain an organic antistatic agent; mixing 8g of functionalized graphene, 4.2g of organic antistatic agent, 0.1g of p-toluenesulfonamide, and 250g of N,N-dimethylformamide, heating to 140°C in a nitrogen atmosphere, stirring and reacting for 5h, centrifuging after the reaction, washing the obtained precipitate with saturated sodium bicarbonate and deionized water, and drying to obtain a composite antistatic agent;
[0050] Step (3), crushing nylon 6 slices into nylon 6 powder with a particle size of 80 μm, mixing the nylon 6 powder with 3-(4-glycidylbutoxy)-1,2-propylene glycol in a mass ratio of 1:0.1, and mixing at 240° C. and a rotation speed of 50 rpm for 20 min to obtain modified nylon 6; mixing modified nylon 6, dibutyltin dilaurate, a composite antistatic agent, and N,N-dimethylformamide, stirring for 60 min, adding dicyclohexylmethane diisocyanate dropwise at a rate of 0.6 mL / min, reacting at 65° C. for 4 h, filtering after the reaction is completed, washing the filter residue with acetone, and drying to obtain composite modified nylon 6, wherein the mass ratio of modified nylon 6, dibutyltin dilaurate, composite antistatic agent, N,N-dimethylformamide, and dicyclohexylmethane diisocyanate is 1:0.005:0.15:50:0.03;
[0051] Step (4), melt spinning the composite modified nylon 6 to obtain composite modified nylon 6 fiber, spinning the composite modified nylon 6 fiber into yarns of different finenesses, dehydrating the yarns after heat setting treatment, and then weaving them into grey cloth; wherein, the melt spinning process conditions are: a spinneret with a micropore diameter of 0.22 mm and an aspect ratio of 3:1 is selected, the spinning temperature is 270°C, and the spinning traction speed is 4000m / min; the heat setting process conditions are: heating to 140°C at a rate of 4°C / min, then heating to 180°C at a rate of 1°C / min, and keeping warm for 60min; in the grey cloth: the yarn count of the warp yarn is 28dTex, the warp density is 205 yarns / inch, and the yarn count of the weft yarn is 87dTex, and the weft density is 42 yarns / inch;
[0052] Step (5): the grey cloth is treated with a composite finishing liquid, dyed and finished, and then subjected to product shaping and pre-shrinking finishing to obtain a low shrinkage and wrinkle-resistant nylon cloth; wherein the product shaping adopts the same process method as the heat setting treatment in step (4); the pre-shrinking finishing is carried out using a rubber blanket pre-shrinking machine under the conditions of a pressure of 5 MPa and a temperature of 150° C., and a speed of 60 m / min; the dyeing and finishing method is: dyeing with an acid dye at 90° C. and standing for 3 hours; the amount of acid dye used is: 13 g of dye material for 1 kg of grey cloth; the composite finishing liquid finishing method is: immersing the dyed grey cloth in the finishing liquid, the bath ratio is 1:20, the finishing temperature is 60° C., the finishing time is 40 min, and after the finishing is completed, it is first dried at 70° C. for 3 minutes, and then cured at 140° C. for 5 minutes.
[0053] Example 4
[0054] This embodiment discloses a method for preparing a low shrinkage and wrinkle-resistant nylon fabric, comprising the following steps:
[0055] Step (1), dispersing 7.5 g of graphene powder in 650 g of 70% ethanol aqueous solution, purging with nitrogen and ultrasonically treating for 30 min, adding 3.5 g of L-cysteine and 0.5 g of azobisisobutyronitrile, purging with nitrogen and ultrasonically treating for 30 min each, heating to 65° C. and reflux reaction for 10 h, after the reaction is completed, centrifuging, washing, and drying to obtain functionalized graphene;
[0056] Step (2), adding 14.5g lactobionic acid and 26.8g N,N-dimethyldipropylenetriamine to 400g ethanol, heating to 160°C in a nitrogen atmosphere, reflux reaction for 12h, rotary evaporation to remove the solvent, washing the obtained product with ether 4 times, and drying to obtain an intermediate; mixing 30.2g of the intermediate, 25g of chloropropane, and 400g of methanol, reacting at 39°C for 25h, rotary evaporation to remove the solvent, washing the obtained product with ether 4 times, and drying to obtain an organic antistatic agent; mixing 6.5g of functionalized graphene, 3.2g of organic antistatic agent, 0.08g of p-toluenesulfonamide, and 200g of N,N-dimethylformamide, heating to 130°C in a nitrogen atmosphere, stirring and reacting for 4h, centrifuging after the reaction, washing the obtained precipitate with saturated sodium bicarbonate and deionized water, and drying to obtain a composite antistatic agent;
[0057] Step (3), crushing nylon 6 slices into nylon 6 powder with a particle size of 60 μm, mixing the nylon 6 powder with 3-(4-glycidylbutoxy)-1,2-propylene glycol in a mass ratio of 1:0.08, and mixing at 235° C. and a rotation speed of 40 rpm for 15 minutes to obtain modified nylon 6; mixing modified nylon 6, dibutyltin dilaurate, a composite antistatic agent, and N,N-dimethylformamide, stirring for 45 minutes, adding dicyclohexylmethane diisocyanate dropwise at a rate of 0.5 mL / min, reacting at 60° C. for 3 hours, filtering after the reaction is completed, washing the filter residue with acetone, and drying to obtain composite modified nylon 6, wherein the mass ratio of modified nylon 6, dibutyltin dilaurate, composite antistatic agent, N,N-dimethylformamide, and dicyclohexylmethane diisocyanate is 1:0.003:0.1:35:0.025;
[0058] Step (4), melt spinning the composite modified nylon 6 to obtain composite modified nylon 6 fiber, spinning the composite modified nylon 6 fiber into yarns of different finenesses, dehydrating the yarns after heat setting treatment, and then weaving them into grey cloth; wherein, the melt spinning process conditions are: a spinneret with a micropore diameter of 0.2 mm and an aspect ratio of 3:1 is selected, the spinning temperature is 265°C, and the spinning traction speed is 3500m / min; the heat setting process conditions are: heating to 110°C at a rate of 3.3°C / min, then heating to 150°C at a rate of 1°C / min, and keeping warm for 45min; in the grey cloth: the yarn count of the warp yarn is 25dTex, the warp density is 218 yarns / inch, and the yarn count of the weft yarn is 84dTex, and the weft density is 45 yarns / inch;
[0059] Step (5), after the grey cloth is treated with a composite finishing liquid and dyed, it is then subjected to product shaping and pre-shrinking finishing to obtain a low shrinkage and wrinkle-resistant nylon cloth; wherein the product shaping adopts the same process method as the heat setting treatment in step (4); the pre-shrinking finishing is carried out using a rubber blanket pre-shrinking machine under the conditions of a pressure of 4.5 MPa and a temperature of 145° C., and a speed of 50 m / min; the dyeing and finishing method is: dyeing with an acid dye at 85° C., standing for 2.5 hours, and the amount of acid dye used is: 10 g of dye material per kg of grey cloth; the composite finishing liquid finishing method is: immersing the dyed grey cloth in the finishing liquid, the bath ratio is 1:17.5, the finishing temperature is 55° C., the finishing time is 30 min, and after the finishing is completed, it is first dried at 65° C. for 1-3 min, and then cured at 135° C. for 2-5 min.
[0060] The composite finishing liquid used in the above Examples 2-4 is the composite finishing liquid prepared in Example 1.
[0061] Comparative Example 1
[0062] Comparative Example 1 Compared with Example 1, in the process of preparing the composite finishing liquid in Comparative Example 1, modified sericin was used instead of hybrid modified sericin, and other conditions remained unchanged.
[0063] Comparative Example 2
[0064] Comparative Example 2 Compared with Example 1, in the process of preparing hybrid modified sericin in Comparative Example 2, sericin was used instead of modified sericin, and other conditions remained unchanged.
[0065] Comparative Example 3
[0066] Comparative Example 3 Compared with Example 1, in the process of preparing the composite finishing liquid, the modified nanosilver is used instead of the hybrid modified sericin, and other conditions remain unchanged.
[0067] Comparative Example 4
[0068] Comparative Example 4 Compared with Example 4, Comparative Example 4 adopts the composite finishing liquid prepared in Comparative Example 1, and other conditions remain unchanged.
[0069] Comparative Example 5
[0070] Comparative Example 5 Compared with Example 4, Comparative Example 5 adopts the composite finishing liquid prepared in Comparative Example 2, and other conditions remain unchanged.
[0071] Comparative Example 6
[0072] Comparative Example 6 Compared with Example 4, Comparative Example 6 adopts the composite finishing liquid prepared in Comparative Example 3, and other conditions remain unchanged.
[0073] Comparative Example 7
[0074] Compared with Example 4, in Comparative Example 7, graphene was not functionalized, and in the preparation of the composite antistatic agent, graphene was directly mixed with the organic antistatic agent to prepare the composite antistatic agent, and other conditions remained unchanged.
[0075] Comparative Example 8
[0076] Compared with Example 4, in Comparative Example 8, an organic antistatic agent is used instead of a composite antistatic agent during the preparation of composite modified nylon 6, and other conditions remain unchanged.
[0077] Comparative Example 9
[0078] Comparative Example 9 Compared with Example 4, in Comparative Example 9, no lactobionic acid was added during the preparation of the organic antistatic agent, and other conditions remained unchanged.
[0079] Comparative Example 10
[0080] Compared with Example 4, in Comparative Example 10, functionalized graphene is used instead of the composite antistatic agent during the preparation of the composite modified nylon 6, and other conditions remain unchanged.
[0081] In the above embodiments and comparative examples, graphene powder, with a particle size of 50-300nm and a brand name of 9592, comes from Shanghai Yingfeng Ruihuang Metal Materials Co., Ltd.; nylon 6 chips, with a brand name of BASF of Germany and a brand name of 8233G HS, come from Shanghai Chaoqi Plastics Co., Ltd.; 3-(4-glycidylbutoxy)-1,2-propanediol, with a CAS number of 139471-23-1, comes from Hubei Kangxinyuanshun Pharmaceutical Chemical Co., Ltd.; sericin powder, with a CAS number of 60650-88-6 and a molecular weight of 5000, comes from Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.; nanosilver, with a particle size of 20nm-80nm, model CB2311, comes from Wuhan Lvjing Fenghua Biotechnology Co., Ltd.; acid dye, model WF300, with a range of uses: wool, nylon, wool, silk, nylon, etc., comes from Shenzhen Yongfa Chemical Co., Ltd.
[0082] Experimental example
[0083] The performance of the low shrinkage and wrinkle-resistant nylon fabrics prepared in Examples 2-4 and Comparative Examples 4-10 was tested.
[0084] 1. Shrinkage test: Refer to the standard AATCC 135-2015 "Dimensional Changes of Fabrics in Home Washing" to test the shrinkage after dyeing.
[0085] 2. Wrinkle resistance test: Refer to the standard AATCC 66-2017, and test the wrinkle recovery angle of samples with a size of 40mm×15mm, and take the average value.
[0086] 3. Antistatic test: Use LFY-406 fabric surface resistivity tester to test the surface resistivity of the sample after 30 washes.
[0087] The test results are shown in Table 1:
[0088]
[0089] It can be seen from the test results in Table 1 that the low shrinkage and wrinkle-resistant nylon fabrics prepared in Examples 2-4 of the present invention have excellent wrinkle resistance and durable antistatic properties, and the shrinkage after dyeing is as low as less than 1.22%. From the comparison between comparative example 4 and example 4, it can be seen that the nanosilver in the hybrid modified sericin has a significant effect on the antistatic property of the nylon cloth; from the comparison between comparative examples 5-6 and example 4, it can be seen that the amino, carboxyl and hydroxyl groups in the sericin can increase the hydrophilicity and improve the antistatic property, and improve the antistatic property by improving the dispersion of the nanosilver by improving the binding of the nanosilver. Furthermore, after the sericin is modified, the amino, carboxyl, hydroxyl groups and carbon-carbon double bonds are cross-linked with the amino and hydroxyl groups of the composite modified nylon 6 fiber through chemical bonds or hydrogen bonds, thereby improving the wrinkle resistance of the nylon cloth and reducing the shrinkage rate; from the comparison between comparative examples 7-8 and example 4, it can be seen that the addition of graphene can improve the antistatic property and dimensional stability of the nylon 6 fiber, so that the nylon cloth has good antistatic property, wrinkle resistance and low shrinkage rate. Furthermore, by functionalizing the graphene, the introduction of Hydrophilic carboxyl and amino groups are introduced, and reactive groups (carboxyl groups) are provided for the combination with the organic antistatic agent, so as to realize the covalent combination of the organic antistatic agent and the inorganic antistatic agent, solve the interfacial compatibility problem between the inorganic graphene and nylon 6, and improve the efficacy of the graphene; from the comparison between comparative example 9 and example 4, it can be seen that the abundant hydroxyl groups in the lactobionic acid structure of the organic antistatic agent can not only improve the hydrophilicity, but also provide reactive groups for the grafting of functionalized graphene, and more importantly, hydroxyl groups are introduced into the composite modified nylon 6 to realize the crosslinking between 1,3,5-triacryloylhexahydro-1,3,5-triazine, hybrid modified sericin and nylon cloth fibers, thereby affecting the wrinkle resistance, antistatic property and shrinkage rate of the nylon cloth; from the comparison between comparative example 10 and example 4, it can be seen that the antistatic effect of the organic antistatic agent is significant, and the diquaternary ammonium salt structure has a significant effect on its antistatic effect.
[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low shrinkage and wrinkle-resistant nylon fabric, characterized in that: The following steps are involved: Step (1), modifying graphene with L-cysteine to obtain functionalized graphene; Step (2), lactobionic acid reacts with N,N-dimethyldipropylenetriamine to obtain an intermediate; the intermediate reacts with chloropropane to obtain an organic antistatic agent; functionalized graphene is combined with the organic antistatic agent to obtain a composite antistatic agent; Step (3), first modifying nylon 6 with 3-(4-glycidylbutoxy)-1,2-propylene glycol to prepare modified nylon 6, and then treating the modified nylon 6 with a composite antistatic agent to obtain composite modified nylon 6; wherein the preparation step of composite modified nylon 6 comprises: mixing and stirring modified nylon 6, dibutyltin dilaurate, the composite antistatic agent, and N,N-dimethylformamide, adding dicyclohexylmethane diisocyanate, reacting, filtering, washing, and drying after the reaction is completed to obtain composite modified nylon 6; Step (4), the composite modified nylon 6 is melt-spun to obtain composite modified nylon 6 fibers, the composite modified nylon 6 fibers are spun into yarns, the yarns are heat-set and then dehydrated, and then woven into grey fabrics; Step (5), after the grey cloth is treated with a composite finishing liquid and dyed, it is then subjected to product finalization and pre-shrinkage finishing to obtain a low shrinkage and wrinkle-resistant nylon cloth; wherein the method for preparing the composite finishing liquid comprises the following steps: step S1, modifying sericin with acryloyl chloride to obtain modified sericin; step S2, modifying nanosilver with a silane coupling agent KH-550 to obtain modified nanosilver; the modified sericin reacts with the modified nanosilver to obtain a hybrid modified sericin; step S3, using 1,3,5-triacryloylhexahydro-1,3,5-triazine and hybrid modified sericin as raw materials to prepare a composite finishing liquid.
2. The method for preparing low shrinkage and wrinkle-resistant nylon fabric according to claim 1, characterized in that: In the step (1), the functionalized graphene preparation method comprises dispersing graphene powder in an ethanol aqueous solution with a volume fraction of 70%, purging with nitrogen and ultrasonically treating for 20-40 minutes, adding L-cysteine and azobisisobutyronitrile, purging with nitrogen and ultrasonically treating for 20-40 minutes respectively, heating to 60-70°C for reflux reaction for 8-12 hours, and after the reaction is completed, centrifuging, washing, and drying; wherein the mass ratio of graphene powder, ethanol aqueous solution, L-cysteine, and azobisisobutyronitrile is (5-10): (500-800): (2-5): (0.4-0.6).
3. The method for preparing the low shrinkage and wrinkle-resistant nylon fabric according to claim 1, characterized in that: In the step (2), the preparation method of the organic antistatic agent is as follows: lactobionic acid and N,N-dimethyldipropylenetriamine are added to ethanol, heated to 150-170°C in a nitrogen atmosphere, refluxed for 10-15h, rotary evaporated, washed, and dried to obtain an intermediate; wherein the mass ratio of lactobionic acid, N,N-dimethyldipropylenetriamine, and ethanol is (11.6-17.4):(19.1-34.4):(300-500); the intermediate, chloropropane, and methanol are mixed, reacted at 35-42°C for 20-30h, rotary evaporated, washed, and dried to obtain an organic antistatic agent; wherein the mass ratio of the intermediate, chloropropane, and methanol is (27.5-33):(20-30):(300-500).
4. The method for preparing low shrinkage and wrinkle-resistant nylon fabric according to claim 1, characterized in that: In the step (2), the preparation method of the composite antistatic agent is as follows: functionalized graphene, organic antistatic agent, p-toluenesulfonamide, and N,N-dimethylformamide are mixed, heated to 120-140° C. in a nitrogen atmosphere, and stirred for reaction for 3-5 hours. After the reaction is completed, the mixture is centrifuged, and the obtained precipitate is washed with saturated sodium bicarbonate and deionized water, and then dried to obtain the composite antistatic agent; wherein the mass ratio of functionalized graphene, organic antistatic agent, p-toluenesulfonamide, and N,N-dimethylformamide is (5-8): (2.1-4.2): (0.05-0.1): (150-250).
5. The method for preparing low shrinkage and wrinkle-resistant nylon fabric according to claim 1, characterized in that: In the step (3), the preparation method of the composite modified nylon 6 is as follows: nylon 6 slices are crushed into nylon 6 powder with a particle size of 30-80 μm, the nylon 6 powder is mixed with 3-(4-glycidylbutoxy)-1,2-propylene glycol at a mass ratio of 1:(0.06-0.1), and the mixture is mixed at 230-240° C. and a rotation speed of 30-50 rpm for 10-20 min to obtain modified nylon 6; the modified nylon 6, dibutyltin dilaurate, and the composite modified nylon 6 are mixed. The composite antistatic agent and N,N-dimethylformamide are mixed, stirred for 30-60 minutes, dicyclohexylmethane diisocyanate is added dropwise at a rate of 0.3-0.6 mL / min, and the reaction is carried out at 55-65°C for 2-4 hours. After the reaction is completed, the mixture is filtered, and the filter residue is washed with acetone and dried to obtain a composite modified nylon 6, wherein the mass ratio of modified nylon 6, dibutyltin dilaurate, composite antistatic agent, N,N-dimethylformamide and dicyclohexylmethane diisocyanate is 1: (0.002-0.005): (0.05-0.15): (20-50): (0.02-0.03).
6. The method for preparing low shrinkage and wrinkle-resistant nylon fabric according to claim 1, characterized in that: In the step (4), the melt spinning process conditions are: a spinneret with a micropore diameter of 0.18-0.22 mm and an aspect ratio of 3:1, a spinning temperature of 260-270°C, and a spinning traction speed of 3000-4000 m / min; the heat setting treatment process conditions are: heating to 80-140°C at a rate of 2.5-4°C / min, then heating to 120-180°C at a rate of 1°C / min, and keeping warm for 30-60 min; in the grey cloth: the warp yarn count is 22-28 dtex, the warp density is 205-231 yarns / inch, the weft yarn count is 81-87 dtex, and the weft density is 42-48 yarns / inch.
7. The method for preparing low shrinkage and wrinkle-resistant nylon fabric according to claim 6, characterized in that: In the step (5), the product shaping is carried out in the same process as the heat setting treatment in the step (4); the pre-shrinkage finishing is carried out under the conditions of a pressure of 4-5 MPa and a temperature of 140-150°C, and a vehicle speed of 40-60 m / min; the dyeing and finishing method is: dyeing with an acid dye at 80-90°C and standing for 2-3 hours; the amount of acid dye used is 7-13 g of dye material per 1 kg of grey cloth; the composite finishing liquid finishing method is: immersing the dyed grey cloth in the finishing liquid, the bath ratio is 1:(15-20), the finishing temperature is 50-60°C, the finishing time is 20-40 min, and after the finishing is completed, it is first dried at 60-70°C for 1-3 min, and then cured at 130-140°C for 2-5 min.
8. The method for preparing low shrinkage and wrinkle-resistant nylon fabric according to claim 1, characterized in that: In step (5), the method for preparing the composite finishing liquid comprises the following steps: Step S1, adding sericin powder to a 0.13wt% sodium chloride aqueous solution, stirring until all solids are dissolved, adding acryloyl chloride at 0-5°C, stirring for reaction for 50-80min, stirring for reaction at room temperature for 100-150min, dialyzing, and freeze-drying to obtain modified sericin; wherein the mass ratio of sericin powder, sodium chloride aqueous solution, and acryloyl chloride is (1.8-3.6): (100-150): (0.07-0.14); Step S2, adding a silane coupling agent KH-550 solution to a 2.5-10wt% nano-silver ethanol dispersion, stirring for 20-40 minutes, stirring and reacting at 60-80°C for 4-6 hours, centrifuging after the reaction, washing, and drying to obtain modified nano-silver; wherein the silane coupling agent KH-550 solution is obtained by mixing silane coupling agent KH-550, deionized water, and ethanol in a mass ratio of 2.5:1:9, and then adjusting the pH to 4 with acetic acid; the mass ratio of silane coupling agent KH-550 to nano-silver is (0.01-0.02):1; adding modified sericin and modified nano-silver to the mixture; Put it into water and stir for 20-40 minutes. At room temperature, add 0.2g / mL 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution at a rate of 1.5-2.5mL / min. Stir and react for 20-25h. After the reaction is completed, remove the upper liquid after centrifugation, wash and dry to obtain hybrid modified sericin. The amount ratio of modified sericin, modified nanosilver, water and 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution is (2-3) g: (0.8-1.2) g: (100-200) g: (3-4.5) mL. Step S3, adding 1,3,5-triacryloylhexahydro-1,3,5-triazine to a sodium bicarbonate aqueous solution with a concentration of 20 g / L, heating to 50-60° C., stirring for 20-40 min, and then adding hybrid modified sericin to obtain a composite finishing solution, wherein the concentration of 1,3,5-triacryloylhexahydro-1,3,5-triazine in the composite finishing solution is 80-120 g / L, and the concentration of the hybrid modified sericin is 5-15 g / L.
9. A low-shrinkage and wrinkle-resistant nylon fabric prepared by the method for preparing a low-shrinkage and wrinkle-resistant nylon fabric as claimed in any one of claims 1 to 8.
10. Use of the low shrinkage and wrinkle-resistant nylon fabric as claimed in claim 9 in a zipper.
Citation Information
Patent Citations
Method for preparing quaternary ammonium salt group-loading graphene oxide material prepared by two-step method, and applications thereof
CN110586034A
Graphene-containing conductive antibacterial nylon composite fiber as well as preparation method and application thereof
CN114381821A